Exploring the Effects of Personality Traits on the Perception of Emotions From Prosody - Furnes, Desire; Berg, Hege; Mitchell, Rachel M.; Paulmann, Silke (Frontiers in Psychology, 2019)
It has repeatedly been argued that individual differences in personality influence emotion processing, but findings from both the facial and vocal emotion recognition literature are contradictive, suggesting a lack of reliability across studies. To explore this relationship further in a more systematic manner using the Big Five Inventory, we designed two studies employing different research paradigms. Study 1 explored the relationship between personality traits and vocal emotion recognition accuracy while Study 2 examined how personality traits relate to vocal emotion recognition speed. The combined results did not indicate a pairwise linear relationship between self-reported individual differences in personality and vocal emotion processing, suggesting that the continuously proposed influence of personality characteristics on vocal emotion processing might have been overemphasised previously.